Class I TCP transcription factors activate the SAUR63 gene subfamily in gibberellin-dependent stamen filament elongation - Gastaldi, Victoria (2020)
In autogamous plants like Arabidopsis (Arabidopsis thaliana), stamen filament elongation must be finely regulated to ensure that anthers reach the pistil at the correct developmental stage. In this work, we studied the roles of Arabidopsis TEOSINTE BRANCHED1, CYCLOIDEA, PCF15 (TCP15), and related class-I TCP transcription factors in stamen filament elongation. Plants with decreased expression of class-I TCPs and plants that express a fusion of TCP15 to a repressor domain (pTCP15::TCP15-EAR) had shorter stamens, indicating that class-I TCPs stimulate filament growth. These plants also showed reduced expression of several SMALL AUXIN UP RNA (SAUR)63 subfamily genes, which contain TCP target motifs in their promoters. Mutational analysis indicated that the TCP target motif in the SAUR63 promoter is required for expression of SAUR63 in stamen filaments. Moreover, TCP15 directly binds to the SAUR63 promoter region that contains the TCP target motif in vivo, highlighting the role of the TCPs in this process. Class-I TCPs are also required for the induction of SAUR63 subfamily genes by gibberellins (GAs). In addition, overexpression of SAUR63 restores filament growth in pTCP15::TCP15-EAR plants, whereas overexpression of TCP15 rescues the short stamen phenotype of GA-deficient plants. The results indicate that TCP15 and related class-I TCPs modulate GA-dependent stamen filament elongation by direct activation of SAUR63 subfamily genes through conserved target sites in their promoters. This work provides insight into GA-dependent stamen filament elongation.